Kajian Eksperimental dan Numerikal Kekuatan dan Daktilitas Mortar-filled Hollow Column akibat Beban Aksial Konsentris - Sandy Immanuel Yansiku; Yohanes G. G. L. Duran; Anjeli Dos Santos (Universitas Batanghari Jambi, 2026)
The axial load-carrying capacity of hollow concrete columns significantly decreases when the wall thickness is inadequate, leading to premature crushing or instability of the outer shell. The internal void causes the column wall to behave as a thin shell structure, rendering it susceptible to local buckling and stiffness degradation. Several structural failures, particularly in hollow pile foundations and prestressed concrete poles, have been attributed to this reduction in load-bearing capacity. This study aims to evaluate the effectiveness of mortar infill as an internal strengthening technique to enhance the strength and ductility of hollow concrete columns while maintaining a reduced self-weight. The research employs both experimental and numerical approaches. The experimental program involves axial compression tests on eleven hollow cylindrical specimens with varying wall thicknesses and mortar infill configurations. Complementary finite element analyses are conducted to calibrate a material constitutive model consistent with the experimental behavior, followed by the development of a numerical interaction diagram tailored for hollow column systems. The results demonstrate that mortar infill substantially improves the axial compressive strength, with the extent of enhancement being proportional to the mortar’s compressive strength. Furthermore, the infill induces a more uniform stress distribution and triaxial confinement effect, leading to an improvement of up to 5.6% in lateral performance. Overall, mortar infill is shown to be an effective internal strengthening method that enhances structural stability and delays sudden failure in hollow concrete columns.